2012
DOI: 10.1016/j.neuroimage.2011.08.064
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of T2⁎ anisotropy in white matter fibers in marmoset monkeys

Abstract: T2*-weighted MRI at high field is a promising approach for studying noninvasively the tissue structure and composition of the brain. However, the biophysical origin of T2* contrast, especially in white matter, remains poorly understood. Recent work has shown that R2* (=1/T2*) may depend on the tissue’s orientation relative to the static magnetic field (B0) and suggested that this dependence could be attributed to local anisotropy in the magnetic properties of brain tissue. In the present work, we analyzed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 45 publications
10
81
0
1
Order By: Relevance
“…Modulations of R 2 * with cortex orientation in respect to the B 0 field of 1 Hz were measured in most of the cortex and up to 2-4 Hz in the primary motor, primary visual and associative auditory cortices. These values are significant smaller than the 6 Hz reported in human ex vivo hydrated tissue samples (Oh et al, 2013), 15 Hz reported in vivo in white matter of marmosets (Sati et al, 2012). This should be due not only to the J.P. Marques et al NeuroImage 147 (2017) 152-163 reduced myelination of the cortex (in respect to white matter) but also due to the axonal arrangements in the cortex (running both parallel and perpendicular to the cortex surface) that makes it less anisotropic.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Modulations of R 2 * with cortex orientation in respect to the B 0 field of 1 Hz were measured in most of the cortex and up to 2-4 Hz in the primary motor, primary visual and associative auditory cortices. These values are significant smaller than the 6 Hz reported in human ex vivo hydrated tissue samples (Oh et al, 2013), 15 Hz reported in vivo in white matter of marmosets (Sati et al, 2012). This should be due not only to the J.P. Marques et al NeuroImage 147 (2017) 152-163 reduced myelination of the cortex (in respect to white matter) but also due to the axonal arrangements in the cortex (running both parallel and perpendicular to the cortex surface) that makes it less anisotropic.…”
Section: Discussionmentioning
confidence: 53%
“…In the beginning of the twentieth century, the cytostructure and myelostructure were studied in ex vivo samples using the Nissl and Weissl stain method to unveil the cytostructure (Brodmann, 1909;Sarkissov et al, 1955;von Economo and Koskinas, 1925) and the myelostrucucture (Hopf and Gräfin Vitzthum, 1957;Vogt and Vogt, 1919) of the human cortex. Under the assumption that delimited regions with similar cyto-and myeloarchitecture would lead to specific functions, these groups parcellated the cortex of the human brain into regions, which can be further specified into areas and subareas, with the most well know parcellation being that suggested by Brodmann.…”
Section: Introductionmentioning
confidence: 99%
“…Fukunaga et al (2010) found that extraction of iron results in a reduction of R 2 ⁎ in gray matter. Recent studies have also indicated that myelin is another major source of R 2 ⁎ heterogeneity due to the diamagnetic properties of white matter Liu et al, 2011;Sati et al, 2012). Several groups have reported that R 2 ⁎ decay curve analysis has the potential for myelin quantification (Du et al, 2007;Hwang et al, 2010;van Gelderen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…G radient echo (GE) MRI is widely used in imaging the human brain, because both the phase and magnitude of the complex NMR signal measured with GE sequences can be used to create high-resolution images that show strong contrast between different types of brain tissue (1). Recent studies have shown that there is a direct link between the orientation of the nerve fibers in white matter (WM) with respect to the magnetic field and the contrast observed in magnitude and phase images (2)(3)(4)(5)(6). Although the origin of this link is currently not fully understood, orientation-dependent contrast is of great interest because it could offer researchers access to a new diagnostic tool for investigating tissue microstructure using MRI.…”
mentioning
confidence: 99%